A Modified o-Phthalaldehyde Fluorometric Analytical Method for Ultratrace Ammonium in Natural Waters Using EDTA-NaOH as Buffer. (11th November 2014) - Hu, Hongzhi; Liang, Ying; Li, Shuo; Guo, Qing; Wu, Chancui
Abstract : In the existence of appropriate amount of disodium ethylenediaminetetraacetate (EDTA), precipitation would not occur in seawater and other natural waters even if the sample solution was adjusted to strong basicity, and the NH3 -OPA-sulfite reaction at the optimal pH range could be used to determine ammonium in natural waters. Based on this, a modified o -phthalaldehyde fluorometric analytical method has been established to determine ultratrace ammonium in natural waters. Experimental parameters, including reagent concentration, pH, reaction time, and effect of EDTA, were optimized throughout the experiments based on univariate experimental design. The results showed that the optimal pH range was between 10.80 and 11.70. EDTA did not obviously affect the fluorometric intensity. The linearity range of the proposed method was 0.032–0.500 µ mol/L, 0.250–3.00 µ mol/L, and 1.00–20.0 µ mol/L at the excitation/emission slit of 3 nm/5 nm, 3 nm/3 nm, and 1.5 nm/1.5 nm, respectively. The method detection limit was 0.0099 µ mol/L. Compared to the classical OPA method, the proposed method had the advantage of being more sensitive and could quantify ultratrace ammonium without enrichment.